Co-occurrence of Convergence Insufficiency and Cognitive Impairment in Parkinsonian Disorders: A Pilot Study - Holden, Samantha K.; Van Dok, Erin; Pelak, Victoria S. (Frontiers in Neurology, 2019)
Background: Convergence insufficiency (CI) in parkinsonian conditions causes disabling visual symptoms during near tasks and usually manifests as double vision. Since double vision is more common in patients who report cognitive symptoms, we sought to determine if symptomatic CI, as opposed to asymptomatic CI, could serve as a marker of cognitive impairment in parkinsonian disorders. Methods: Twenty-four participants with parkinsonian disorders (18 Parkinson’s disease, 5 progressive supranuclear palsy, 1 multiple system atrophy) and objective findings of convergence insufficiency on neuro-ophthalmologic examination were included. Subjective visual symptoms and cognitive complaints were recorded, and the Self-Administered Gerocognitive Examination was used as a global cognitive screening measure. Results: 54.1% of parkinsonian participants had cognitive impairment, but there were no significant differences in the degree of convergence insufficiency, measured by near point of convergence (NPC), or cognitive outcomes between those with symptomatic CI and asymptomatic CI. However, NPC was greater for those with cognitive impairment (x=18.4 cm), compared to those who were cognitively intact (x=12.5 cm, p=0.003). Conclusions: Cognitive impairment commonly co-occurs in parkinsonian disorders with convergence insufficiency and is associated with significantly greater NPC distances. Clinicians should have a high index of suspicion for cognitive impairment in patients with objective findings of convergence insufficiency, whether symptomatic or not. Further investigation of convergence insufficiency in relationship to cognitive impairment in parkinsonian disorders is warranted, as there may be a shared mechanism of dysfunction.